Comparative Flower Pigment Study of Orchid Plants - Tan, Suat Hian; Shahida, Abdul Manap; Karim, Md. Rezaul; Rashid, Shah Samiur; Maziah, Mahmood; Ma, Nyuk Ling (AENSI Journals, 2014)
Background: Orchidaceae species has developed into one of the significant industrial products in agricultural industry globally. Beside as potted flower, they serve as cut flowers since they have eye-catching pigments in the flower petals. Objective: The main pigments from orchid’s flower petals were investigated and their relations with phenylalanine ammonia-lyase (PAL) activity were evaluated. Results: Total anthocyanin content of six different orchids’ petals was determined specthrophotometrically and the value ranged from 0 mg/g (in Dendrobium Shavin white) to 2.128 mg/g (in Mokara Aranda). Total anthocyanin content was found to be the highest when compare to β-carotene and chlorophyll content. In correlation analysis, PAL activity was found to be significant positive correlated with the anthocyanin content. Conclusion: The results indicate the potential for PAL enzyme as a biomarker for flower colour in orchids.